Influence of the Duration of Intravenous Drug Administration on Tumor Uptake - Fouliard, Sylvain; Chenel, Marylore; Marcucci, Fabrizio (Frontiers in Oncology, 2013)
Enhancing tumor uptake of anticancer drugs is an important therapeutic goal, because insufficient drug accumulation is now considered to be an important reason for unresponsiveness or resistance to antitumor therapy. Based on a mechanistic tumor uptake model describing tumor exposure to molecules of different molecular size after bolus administration, we have investigated the influence of the duration of intravenous administration on tumor uptake. The model integrates empirical relationships between molecular size and drug disposition (capillary permeability, interstitial diffusivity, available volume fraction and plasma clearance), together with a compartmental pharmacokinetics model and a drug/target binding model. Numerical simulations were performed using this model for protracted intravenous drug infusion, a common mode of administration of anticancer drugs. The impact of the administration on tumor uptake is described for a large range of molecules of different molecular size. Evaluation was not only on the maximal drug concentration achieved in the tumor, but also on the dynamic profile of drug concentration. It is shown that despite a lower maximal uptake for a given dose, infusion allows a prolonged exposure of tumor tissues to both small- and large-sized molecules. Moreover, infusion may allow higher doses to be administered by reducing Cmax-linked toxicity, thereby allowing a similar maximal uptake compared to bolus administration.